Dielectro Phoretic Force Spectroscopy in Short Blood Cell Aggregations - Ramirez, Araceli; Corro, Griselda; Flores, Esteban Molina (British Journal of Healthcare and Medical Research, 2025)
Aggregation of red blood cells and specifically linear rouleau formation of human erythrocytes affects the rheology of blood microcirculation and is widely under study to quantify flow abnormality in pathological conditions. Dielectric properties of cell suspensions or of undiluted whole blood are strongly related to the geometrical structure of particles. Electrophoretic measurements of rouleaux, formed through side-by-side adhesion of a small or even considerable number of erythrocytes, in suspending media of different electrical conductivity have the potential of size characterization and spatial separation of cell subpopulations due to their different polarizabilities. In the present paper we show that the electrophoretic force on red blood cell aggregations of different sizes, exposed to an electric field of variable frequency, and given correct medium permittivity and conductivity, provides a means for spatial separation and sorting of rouleaux with different ‘stack number’ of aggregated erythrocytes. In dependence on this number, i.e. on different but discrete measures of rouleau lengths, the dielectrophoretic force is calculated and represented against the frequency of the applied a.c. field. Predictions of frequency regions in the range of 10 to 100 MHz are made, where the amount and the direction of dielectrophoresis forces is different for different rouleau sizes. The field-flow-fractionation technique is a suitable tool, where the differential positioning of particles of definite size within a suspension flow velocity profile is established by the action of matching dielectrophoretic forces. Increased aggregation of red blood cells is considered an important factor in the development of vascular diseases and microcirculation impairment. The progressing diversity and size of rouleaux characterized by their 'stack number' might be a possible diagnose tool in the assessment of abnormal rheological properties.